Kaizen in Improving the Productivity of Garment Sewing - Reza, Md. Alimur; Swarna, Sabrina Shahrin; Aktar, Rozina; Rashid, Kazi Mamunur; Dola, Dilshat Rubia; Tasnim, Lamia; Altaf, Habiba (European Scientific Journal, ESJ, 2023)
One of the most crucial strategies for managing continuous improvement is kaizen. Because lowering cycle times and manufacturing costs is our goal. One of the first steps in that direction is the elimination of bottlenecks in the production line. In order to go toward our goal, a meeting was first scheduled with the production and IE teams to explore potential areas for improvement. Then, using a time study and a capacity graph, we determined the workable area. By videotaping the bottleneck process, analyzing the arrangement of the workstations, and managing the machines, we were able to assess the micro-movements. Then, in order to improve the procedure, we shared the motion economy and point kaizen concepts with the relevant department and scheduled a training session for the staff. We implemented the improved method on the selected workstations. At last, the follow-up responsibility was handed over to the responsible authority.